Pareto-Criterion and Impact Evaluation of Covid-19 Pandemic on Nigeria Educational System (2021)
Impact evaluation of COVID-19 challenges on Nigeria educational system is the focus of this paper. There are various reasons for assessment of this pandemic; however, the major reason is to document it for future generation. This study therefore, examined the impacts of COVID-19 pandemic on Nigeria educational system. The study was conducted using volunteering sampling technique and 1080 participants were used using telephone and online methods of inquiry. Those who completed the interview were 654 (60.6%) males and the rest 426 (39.4%) were female respondents. The instrument has 32 items and a reliability coefficient of .78. Some of the impacts of COVID-19 on Nigeria educational system are: school closure, stoppage of teaching-learning process, disruption of school calendar, wastages on destructive materials bought for teaching-learning process, salaries were paid for job not done, some academic staff lost their jobs most especially those in private schools due to lack of salary to pay them, many students had died due to COVID-19, it leads to wastages of students time, some students cannot embark on their education due to the facts that some of them had been put into family way, both internal and external examination had been suspended for future date, educational school calendar has to be readjusted, virtual learning and open distance learning are the order of the day, its leads to extra budget to the education stake holders, the learners have been divided into two-the cities and rural dwellers where the virtual learning are not practicable. Based on these findings it was concluded that COVID-19 had negative impact on Nigeria educational system.